Pencemaran Parasit Pada Sayuran di Beberapa Pasar Tradisional Kota Malang - Permata Ika Hidayati; As’ad Syamsul Arifin; Dyah Ayu Widyaningrum (Universitas Insan Budi Utomo, 2022)
Purpose: Vegetables have been reported as a mechanical means of transmission of human intestinal parasites. This study aims to determine the relationship between parasites and vegetables sold in Malang City. Method: Two hundred and fifty (250) vegetables were subjected to sedimentation and zinc sulfate flotation techniques for parasite investigations. Results: Of the 250 vegetables examined, 184 (68.15%) were infected. T. occidentalis had the highest prevalence (9.26%), followed by B. oleracea and D. carota with respective values of 8.89% and 8.15%. The highest parasite prevalence was observed in Pasar Besar (78.89%), followed by Mergan Market (72.22%) and Dinoyo Market (53.33%). Pasar Besar has the highest prevalence of D. carota and C. sativum with a prevalence of 11.11 and 10.00%, respectively. Statistically, there were no significant differences in contaminated vegetables (p > 0.05) but significant differences were seen at market locations (p < 0.05). The highest percentage of parasite occurrence was A. lumbricoides with an occurrence percentage of 23.49. The most common parasites in the Big Market are Ascaris lumbricoides (45.56%) and Entamoeba histolytica (30.00%). There was a significant effect (p < 0.05) on parasite prevalence (p = 0.0003; df = 6; F = 11.07) and market location (p = 0.0019; df = 2; F = 11.01 ). Main component analysis shows that the location of the study has a positive effect on the incidence of parasites with the Big Market location of 95.99% of the total variance. Further analysis showed that A. lumbricoides , Trichuris trichura , and hookworm prevalence were strongly correlated with the location of Pasar Besar and Pasar Dinoyo . Conclusion: Given the public health importance of isolated parasites, there is a need to improve environmental sanitation, personal hygiene and surveillance systems in vegetable transportation, storage and display facilities in Malang City in general.